Diversi Dalam Penanganan Anak Yang Berkonflik Dengan Hukum Dalam Sistem Peradilan Pidana Anak - Ingratubun, Yerusalina; Toule, Elsa Rina Maya; Wadjo, Hadibah Zachra (PATTIMURA Legal Journal, 2023)
Introduction: Children in conflict with the law in the juvenile criminal justice system, the form of settlement is with a restorative justice approach through diversion which is an initial step in the settlement process before proceeding to the next legal process. Purposes of the Research: This study aims to analyze and examine the implementation of diversion in handling children in conflict with the law. Methods of the Research: The type of research used in this research is empirical. Sources of data include primary data and secondary data. Data collection techniques through interviews and literature study and data analysis using qualitative analysis. Results of the Research: The results showed that the implementation of diversion in handling criminal acts committed by children was in accordance with what was mandated by the Juvenile Criminal Justice System Act at the stages of investigation, prosecution and trial. If the settlement of a criminal case committed by a child through diversion is successful in peace between the parties, the report will be revoked because there has been a mutual agreement in the peace made. The settlement process with this diversion did not all run smoothly and succeeded in reaching a peace agreement between the parties. If the diversion process does not result in an amicable agreement or the diversion agreement is not implemented, then the juvenile criminal justice process will proceed to the Court. In the settlement of criminal cases committed by children, there are still obstacles faced by law enforcement officers and litigants and there are still factors that hinder the implementation of diversion.